(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Bharati Mukherjee was born on July 27, 1940, to anupper-middle class Hindu Brahmin family in Calcutta, India. The second of threedaughters of Sudhir Lal, a chemist, and Bina (Banerjee) Mukherjee, she livedwith 40 or 50 relatives until the age of eight. Born into an extraordinarilyclose-knit and intelligent family, Mukherjee and her sisters were always givenample academic opportunities, and thus have all pursued academic endeavors intheir careers and have had the opportunity to receive excellent schooling. In1947, her father was given a job in England and he brought his family to livethere until 1951, which gave Mukherjee an opportunity to develop and perfecther English language skills.